Pengaruh Model Guided Discovery Learning Dengan Metode Eksperimen Terhadap Hasil Belajar Fisika Peserta Didik MAN 1 Mataram Ditinjau Dari Gaya Belajar VAK - Suci Febriani; Muhammad Taufik; Ni Nyoman Sri Putu Verawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2019)
The aim of this research applied a quasi-experiment by factorial design 2x3 which was conducted to the student of MAN 1 Mataram is to find out the influence of guided discovery learning model combined with experiment method and VAK style due to physics learning outcomes. The population is the students from grade X MIA in MAN 1 Mataram. The sampling technique is using purposive sampling, where, grade X of MIA 1 as an experiment class and grade X of MIA 2 as a control. Data for learning outcomes are measured by applying multiple choice test while learning style of students using a questionnaire Ã¢â¬â the hypothesis test using ANAVA test of two ways supported by SPSS 16 with 5% significance level. According to the analysis results, it can be concluded that: 1) there is an effect of guided discovery learning model with experimental method toward physics learning outcome of students because of sig. <0,05;ÃÂ  2) there is no effect of VAK learning style on physics learning result in MAN students because sig.>0,05; 3) there is no interaction between guided discovery learning model with experiment and VAK learning style method of physics learning result in MAN student because of sig.>0,05.